Análisis del ciclo de vida de los residuos sólidos en obras civiles (2019)
The environmental problems that we are going through today have triggered the concern and awareness for the correct management of solid waste. Civil works are important generators of solid waste and for this reason standards have been created to regulate generation, management, impact, transportation and disposal of such waste. Despite the aforementioned efforts, civil works continue to use bad practices when handling waste. Therefore, it is important and urgent to define the current situation of solid waste management in civil works, analyze the life cycle that is presented and finally analize the possibility of improvement in waste management processes. The above, in order to minimize the negative environmental, social and economic impacts that poor waste management is generating. For the foregoing, first of all the definition of the life cycle analysis that will be handled for this investigation will be presented. Secondly, the stages of the life cycle that will be taken into account will be named. Next step, the current situation that exists in civil works in terms of solid waste management, practices, regulations and life cycles of construction waste will be mentioned. In short, the Simapro program will be used to analyze the environmental impacts caused by solid waste in civil works using quantities of a real project. Given the results of the software, we will proceed to the interpretation, discussion and presentation of possible improvements under the criterion of reduce environmental impacts.